2021
DOI: 10.21512/tw.v22i1.6996
|View full text |Cite
|
Sign up to set email alerts
|

Interrelatedness between Organizational Culture and Human Resource Management in the Context of Corporate Entrepreneurship

Abstract: There has been numerous research carried out on corporate entrepreneurship. This term typically refers to organizational culture or human resource management (HRM). This article was written to supplement previous research that explored the link between entrepreneurship, the culture of organization, and HRM. The purpose of this study is to explain in several related articles the operationalization of the three principles and to explain the interrelationship between them in the context of corporate entrepreneurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Lee et al (2017) found that HR practices and organizational cultural factors independently influence organizational commitment when considered together (Lee et al, 2017;. Maryati et al, 2022) highlighted a symbiotic relationship between HRM policies and organizational culture, emphasizing the importance of aligning these aspects to reduce turnover intention (Maryati et al, 2022;. Naldi et al, 2021) further emphasized the interrelatedness between organizational culture, HRM, and corporate entrepreneurship, suggesting that these elements can mutually influence each other (Naldi et al, 2021).…”
Section: Contextual Factors That Influence the Relationship Between H...mentioning
confidence: 99%
“…Lee et al (2017) found that HR practices and organizational cultural factors independently influence organizational commitment when considered together (Lee et al, 2017;. Maryati et al, 2022) highlighted a symbiotic relationship between HRM policies and organizational culture, emphasizing the importance of aligning these aspects to reduce turnover intention (Maryati et al, 2022;. Naldi et al, 2021) further emphasized the interrelatedness between organizational culture, HRM, and corporate entrepreneurship, suggesting that these elements can mutually influence each other (Naldi et al, 2021).…”
Section: Contextual Factors That Influence the Relationship Between H...mentioning
confidence: 99%